2018
DOI: 10.1186/s13104-018-3498-z
|View full text |Cite
|
Sign up to set email alerts
|

Liver transplant score for prediction of biliary atresia patients’ survival following Kasai procedure

Abstract: ObjectivesRecently, a scoring system has been developed to predict which patients with biliary atresia (BA) who underwent a Kasai procedure should be considered for liver transplant. Here, we applied the scoring system to predict the survival of BA patients following the Kasai procedure at Dr. Sardjito Hospital, Yogyakarta, Indonesia from January 2012 to January 2016.ResultsThere were 26 patients, of whom 14 were males and 12 females. Outcomes of BA patients after the Kasai surgery were 15 survived and 11 died… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…The impact of ascites on morbidity and mortality is well known in adult cirrhotic patients [11,12,17], in whom 1-year and 2-year mortality are nearly 40% and 50%, respectively [17]. Only a very few prior studies have investigated presence of ascites as a prognostic factor in children with cirrhosis [8,22,23]. Pugliese et al [8] studied 522 pediatric patients with end-stage liver disease listed for LT due to several etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…The impact of ascites on morbidity and mortality is well known in adult cirrhotic patients [11,12,17], in whom 1-year and 2-year mortality are nearly 40% and 50%, respectively [17]. Only a very few prior studies have investigated presence of ascites as a prognostic factor in children with cirrhosis [8,22,23]. Pugliese et al [8] studied 522 pediatric patients with end-stage liver disease listed for LT due to several etiologies.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the combined model showed that, when probability >0.66, patients should be prepared for a poor outcome. Several noninvasive serological tests have been suggested to evaluate liver fibrosis in postoperative patients with BA, and determine the optimal timing of LT. 33,34 Serum matrix metalloproteinase-7 has been reported as a novel biomarker for diagnosing BA. However, it has a moderate accuracy of 78.1% for predicting LT. 1 Gunadi et al 33 and Zhen et al 34 developed a liver transplant score, including eight or nine parameters, some of which should be evaluated clinically.…”
Section: Discussionmentioning
confidence: 99%
“…Cholangitis is the most common complication in patients with BA after Kasai surgery, with an incidence of 30%-70% (Gunadi et al, 2018). Several studies have suggested that cholangitis may be a risk factor for poor prognosis in patients with post-Kasai BA (Jiang et al, 2018).…”
Section: Gut Microbiota and Bile Acid Profiles Are Associated With Ja...mentioning
confidence: 99%